Measuring integration and urban sustainability with indicators: Monitoring progress towards integrated public transport - Zsuzsanna Olofsson; Karin Brundell Freij (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
This paper proposes a framework to monitor progress towards improved integration in public transport. The framework adapts some elements of Transport Sustainability Barometer (TSB) which is a tool to assess transport sustainability in Swedish cities. The suggested indicator set follows the complex hierarchy of layers in integration (Process, System, Quality and Use). The selected indicators allow progress to be monitored from two perspectives, objective evidence and citizens' perceptions. The proposed framework is only the first step towards a tool to monitor integration in public transport, and we provide recommendations to further develop a tool in consultation with its intended users.
Keywords: 330; Stadtverkehr; Öffentlicher Nahverkehr; Nachhaltigkeit; Schweden